Comparative effects of Health Qigong and closed motor exercise on the physical and mental health of female drug rehabilitation participants: a randomized controlled trial - Guang Yang; Deyu Meng; Shichun He; Meiqi Wei; Man Li; Lu Zhang; Zhendong Pan; Ziheng Wang (BMC Complementary Medicine and Therapies)
Abstract Background Drug rehabilitation is a challenging process that impacts both the physical and mental health of individuals. Traditional martial arts, such as Health Qigong, and closed motor exercises, such as power cycling, have shown potential benefits in improving health outcomes. This study aims to compare the effects of Health Qigong, closed motor exercises, and their combination on the physical and mental health of female drug rehabilitation participants. Methods In this randomized controlled trial, female participants from the Jilin Province Women’s Compulsory Isolation Drug Rehabilitation Center were randomly assigned to three groups: Health Qigong (QigongG), Closed Motor Exercise (ClosedG), and Combined Health Qigong and Closed Motor Exercise (CombinedG). Measurements were taken at baseline, mid-intervention, and post-intervention and included resting heart rate, vital capacity, choice reaction time, sleep quality, and relapse tendency. Results At the study’s conclusion, the ClosedG group showed significant improvements in relapse tendency, vital capacity, and sleep quality compared to baseline. The QigongG showed significant improvements in relapse tendency, sleep quality, and choice reaction compared to baseline. The CombinedG group demonstrated significant improvements in relapse tendency, vital capacity, sleep quality, and choice reaction time, outperforming the ClosedG groups in reaction time, and outperforming QigongG groups in vital capacity. The CombinedG group exhibited the most notable overall improvements. Conclusion The combined intervention of Health Qigong and closed motor exercises is more effective in improving physical and mental health metrics among female drug rehabilitation participants than either intervention alone. These findings suggest that incorporating a combination of traditional martial arts and closed motor exercises could enhance rehabilitation programs for drug rehabilitation. Trial registration ClinicalTrials.gov NCT06454565. The date of registration is 2024.07.11 (Retrospectively registered).